2009
DOI: 10.1002/app.30694
|View full text |Cite
|
Sign up to set email alerts
|

Optical transparency, thermal resistance, intermolecular interaction, and mechanical properties of poly(styrene‐butadiene‐styrene) copolymer‐based thermoplastic elastomers

Abstract: ABSTRACT:The optical transparency, thermal resistance, intermolecular interaction, and mechanical properties of poly(styrene-block-butadiene-block-styrene) (SBS), which were modified by blending with crystalline polypropylene (PP) or amorphous polystyrene (PS), were analyzed. The dynamic mechanical test indicated that the PP exhibited an intermolecular interaction with SBS and PS was compatible with SBS. The optical properties indicated that the direction of the light was changed due to the difference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 97 publications
(99 reference statements)
0
21
0
1
Order By: Relevance
“…DMA was used in numerous miscibility studies on polymer blends to predict the miscibility of polymer systems in various groups . For an immiscible blend, the tan δ curves generally show the presence of two damping peaks corresponding to the glass transition temperature ( T g ) of individual polymers.…”
Section: Resultsmentioning
confidence: 99%
“…DMA was used in numerous miscibility studies on polymer blends to predict the miscibility of polymer systems in various groups . For an immiscible blend, the tan δ curves generally show the presence of two damping peaks corresponding to the glass transition temperature ( T g ) of individual polymers.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to mechanical properties, tensile and flexural properties of SBS/PP blends, such as yield strength and flexural modulus, would gradually decrease with the gradually increasing content of SBS, whereas the impact strength significantly enhances as well as the elongation at break. Thus, the SBS/PP blends tend to exhibit a more elastomeric nature with the increasing content of SBS . When the blends contain a near equal ratio of each polymer, the morphology of blends presents a intertwined co‐continuous phase structure, and the phase is homodispersed with each other .…”
Section: Introductionmentioning
confidence: 99%
“…Natural rubber and styrene–butadiene–rubber have been applied into the PS matrix to modify the properties of PS, especially its rigid mechanical attributes. Poly(styrene–butadiene–styrene) triblock copolymers ease the process and have unique characteristics that are similar in many ways to those of conventional vulcanized rubber . It has been reported that the phase boundary, relaxation behavior, thermal properties, and mechanical properties of PS were different after it was mixed with styrene–butadiene–styrene (SBS).…”
Section: Introductionmentioning
confidence: 99%
“…Poly(styrene–butadiene–styrene) triblock copolymers ease the process and have unique characteristics that are similar in many ways to those of conventional vulcanized rubber . It has been reported that the phase boundary, relaxation behavior, thermal properties, and mechanical properties of PS were different after it was mixed with styrene–butadiene–styrene (SBS). The addition of SBS improved the impact strength of the PS/SBS system significantly, whereas the tensile strength and tensile modulus were dramatically reduced at the same time .…”
Section: Introductionmentioning
confidence: 99%